PENGARUH JUMLAH KEPADATAN YANG BERBEDA TERHADAP KELULUSHIDUPAN BENIH IKAN MAS (Cyprinus carpio) PADA SISTEM TRANSPORTASI BASAH - Markus L Lake; Agnette Tjendanawangi; Sunadji Sunadji (Nusa Cendana University, 2019)
This study aims to determine the effect of density (Cyprinus carpio) to survival rate of common carp (Cyprinus carpio) with wet transportation system. Research has been conducted on April, 2017. This research used the completely randomized design (CRD) with 3 treatments and 3 replications, namely : A (50 individual/5 liters water), B (100 individual/5 litres water) and C (200 individual/5 liters water). The data was analysed with Analysis of Variance (ANOVA) and Least Significant Different (LSD). The result howed were the highest survival rate obtained treatment by A (85,33%), then treatment B (64%) and treatment C (47,67%). Least significant different (LSD) showed that the treatmens were different significan ly on survival rate at 5% level. Based on the result, it concluse that the density of commin carp give signivicantly effect on the survival rate at wet transportation system. Key words: Carp fish, wet transportation, survival rate.